Musculoskeletal Pain in Parkinson's Disease - Li, Jun; Zhu, Ben-Fan; Gu, Zhu-Qin; Zhang, Hui; Mei, Shan-Shan; Ji, Shao-Zhen; Liu, Shu-Ying; Han, Chao; Chen, Huai-Zhen; Chan, Piu (Frontiers in Neurology, 2022)
Background: Musculoskeletal pain is commonly experienced in patients with Parkinson’s disease. Few studies have investigated the clinical characteristics and risk factors associated with musculoskeletal pain. Objectives: To investigate the distribution, clinical characteristics, and factors associated with musculoskeletal pain in a large sample of patients with Parkinson’s disease. Methods: We enrolled 452 patients from two clinics and used a standardized questionnaire to collect demographic and clinical information. Musculoskeletal pain was diagnosed based on the Ford Classification System, and pain severity was assessed with the numeric rating scale. Multivariate regression models explored the association between clinical features of Parkinson’s disease and quality of life and pain. Results: Two hundred and six patients (45.58%) reported musculoskeletal pain, typically in their lower limbs and backs. Levodopa resulted in a ≥30% reduction in pain intensity scores in 170 subjects. Female sex (odds ratio, 1.57; 95% confidence interval, 1.07–2.29) and Levodopa-equivalent daily doses (odds ratio, 3.35; 95% confidence interval, 1.63–6.59) were associated with an increased risk for musculoskeletal pain. Pain duration (p = 0.017), motor symptoms (p < 0.001), and depression (p < 0.001) were significantly associated with quality of life. Conclusions: The lower limbs and back are common sites of musculoskeletal pain in patients with Parkinson’s disease, and up to 82.52% of patients were responsive to Levodopa. Female sex and Levodopa-equivalent daily doses are associated with musculoskeletal pain, suggesting that dopamine deficiencies, and not motor and non-motor impairment, might be the most critical baseline risk factor of musculoskeletal pain.